In vitro activity of seven hospital biocides against Mycobacterium abscessus: Implications for patients with cystic fibrosis - Steven Caskey (International Journal of Mycobacteriology, 2018)
Background: Mycobacterium abscessus pulmonary infection has recently emerged as a significant pathogen in patients with cystic fibrosis (CF) and is associated with significant morbidity and accelerated pulmonary decline. There is a paucity of data describing the activity of hospital biocides against this organism. Methods: M. abscessus isolates (n = 13) were recovered from CF and non-CF respiratory specimens. Seven commonly employed hospital biocides with generic ingredients as follows: acetone, propan-2-ol, diethylene glycol, 5-chloro-2-methyl-4-isothiazolin-3-one and 2-methyl-4-isothiazolin-3-one, chlorine dioxide, 4% chlorhexidine, alcohol, and disodium carbonate, compound with hydrogen peroxide, 10% sodium hypochlorite were assayed for their biocidal activity against M. abscessus. Fresh cultures of M. abscessus were exposed to biocide in liquid medium as per manufacturers' instruction and were immediately plated following the completion of the contact period. The mean concentration of M. abscessus plated was 9.82 × 106 colony-forming units (range: 1.63 × 105–1.12 × 108). In addition, the remaining bacteria/biocide solution was enriched nonselectively in Mueller Hinton broth (37°C/1 week) and then plated. Results: All M. abscessus isolates survived in alkyl dimethyl benzyl ammonium chloride, 5-chloro-2-methyl-2H-isothiazol-3-one (EC No. 247-500-7) and 2-methyl-2H-isothiazol-3-one, 4% Chlorhexidine™, O-phenylphenol and Sodium Lauryl Sulfate™ and disodium carbonate, compound with hydrogen peroxide. One out of 13 M. abscessus cultures was killed by Chlorine Dioxide™ and one by Sodium Dichloroisocyanurate™, representing a 5-log kill. Two isolates were killed by Alcohol™ again representing a 5 log kill. Following enrichment, O-phenylphenol and Sodium Lauryl Sulfate™ showed the greatest biocidal activity with 11/13 isolates, whereas 2/13 cultures were killed by sodium dichloroisocyanurate™. All other biocide/culture combinations yielded growth. Conclusion: These data indicate that M. abscessus may persist after exposure to several common hospital biocides. Further work is urgently needed to define unequivocal biocide contact treatments to prevent cross-infection with this mycobacterial species in this patient population and thus ensure effective infection control and prevention.